Avaliação de habilidades pré-aritméticas e ensino de adição e subtração para crianças: contribuições da análise do comportamento - Gualberto, Priscila Mara de Araújo (2013)
The purposes of this study were propose: a pre-math skills evaluation tool for map the students repertoire of the early years of elementary school and analyze the complexity of relations of the tool; and an evaluation and teach program of addition and subtraction skills based on equivalence paradigm, describing method, results and behavior analysis on a speech that could foment the intercommunication with professionals other areas, mainly Math Education. Twelve children of the second at fifth years of elementary school participated of the test of the pre-math skills evaluation tool, all of at a public school by Porto Ferreira/SP. The procedure was compound by twelve MTS and CRMTS tasks that tested these relations: discriminations of numerals, number s names and sets; numerals and number s names naming and quantifying of sets; crescent/decrescent ordering of numerals and sets; before/after relations with numerals and sets; major/minor relations with and without sample; more/less relations with and without sample; equality between numerals and sets; relations numeral-set, set-numeral, name-numeral, numeral-name, name-set and set-name; estimate between numerals and sets; sequences completion with sets and numerals. The results demonstrated the tool s viability for identify on the students repertoire gaps that would interfere in later learning, such as addition/subtraction concepts, and allowed us accomplish a behavior analysis of the component skills. Continuing, nine of the same participants were exposed to the MTS procedure that have composed the evaluation and teach program of addition and subtraction skills, grounded on the equivalence paradigm. The program was organized into three units according to difficulty levels, having the unit 1 values from one to ten, the unit 2 values from ten to twenty and the unit 3 values above twenty. The arithmetic operations were composed by stimuli printed numerals, sets and mathematical signs and the relations between them. Eight participants completed the unit 1 and four of these the unit 2 partially and yet two participants concluded the three teach units. The analysis of the results allowed us verify that the subtraction operations were more difficult for some participants, causing greater errors number, and the operations that had the operation s result as sample stimulus showed have been more complex for some them. The evaluation and teach program of addition and subtraction skills made possible the development of a behavioral analysis of these arithmetic operations and the identification of several relevant issues for future studies, such as the role of the signal mathematic in the formation of equivalence classes, the use of strategies on problem solving, the inverse relation between the addition and subtraction operations, the interrelation between the pre-math skills and arithmetic skills, among others.